2012
DOI: 10.1111/j.1742-481x.2012.01071.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of five different dressing materials on split‐thickness skin graft donor site and full‐thickness cutaneous wounds: an experimental study

Abstract: The objective of this study was to investigate the healing effect of five different products on split-thickness skin graft (STSG) donor sites and full-thickness cutaneous wounds (FTCWs) using an occlusive dressing model. Six groups were included: 1 control and 5 experimental groups, with a total of 24 rats, using an occlusive dressing model. STSG donor sites and FTCWs were established in two separate areas, to the right and left on the animals' backs. Wound sites were dressed with one of the following material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Dressing adhesion to skin graft donor site, VAS score, and duration of dressing are presented in Table 2. The mean duration of hospitalization in group A was 17.96±1.4 days (range: 15-21 days), group B, 16.43±1.86 days (range: [13][14][15][16][17][18][19][20], and group C, 16.9±1.55 days (range: [14][15][16][17][18][19][20]. This figure was significantly higher in group A compared with group B and C (P<0.05), but there was no significant difference between groups B and C (P=0.6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dressing adhesion to skin graft donor site, VAS score, and duration of dressing are presented in Table 2. The mean duration of hospitalization in group A was 17.96±1.4 days (range: 15-21 days), group B, 16.43±1.86 days (range: [13][14][15][16][17][18][19][20], and group C, 16.9±1.55 days (range: [14][15][16][17][18][19][20]. This figure was significantly higher in group A compared with group B and C (P<0.05), but there was no significant difference between groups B and C (P=0.6).…”
Section: Resultsmentioning
confidence: 99%
“…Dressing is an acceptable method to protect the wound and reduce the healing duration, pain, infection, and cost [2,16]. Various studies reported that several dressings are appropriate for this aim, including classical gauzes, modern silicone dressing, alginates, and hydrofibers [17].…”
Section: Discussionmentioning
confidence: 99%
“…OPS imaging is a technique based on the optical filtration of polarized light absorbed by hemoglobin (41). This method permits direct in vivo real-time imaging of the capillary network and visualization of the microcirculation in tissues including burned skin (42) and provides qualitative and quantitative information about perfusion because the capillaries are easily visible and red blood cells can be tracked in real time (43,44). This imaging technique has been validated for the measurement of different microcirculatory parameters, in particular FCD, as a parameter of dermal perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…A silk sericin-releasing bioactive dressing [2] for the treatment of proximal thigh STSG donor sites, when compared with a paraffin and chlorhexidine impregnated cotton dressing, was found to be less adherent to the wound, reached full healing 2 days earlier (12 days vs 14 days), and reduced pain in the first 4 postoperative days. Five different dressing materials on STSG donor site healing [3] were examined in an animal model. Fine mesh gauze, microporous polysaccharide hemosphere, clinoptilolite, alginate, hydrogel, and biosynthetic wound dressing (Biobran) were examined for healing rate and quality.…”
Section: Split Thickness Skin Graft (Stsg)mentioning
confidence: 99%